Pengaruh Edukasi Keluarga terhadap Pengetahuan Keluarga dan Kepatuhan Penderita Hipertensi - Tahan, Tahan; Nasution, Siti Zahara; Siregar, Farida Linda Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of family education on family knowledge and compliance with hypertension sufferers in carrying out treatment. The research method used was pre-experiment with a one-group pretest-posttest design approach. The sample in this study amounted to 83 respondents. Data analysis used the Wilcoxon test. The results of research on the influence of family education on family knowledge about hypertension treatment, P-Value < 0.000 and compliance of hypertension sufferers in carrying out P-Value treatment < 0.000. In conclusion, there is an influence of family education on family knowledge and compliance with hypertension sufferers in carrying out treatment. Keywords: Education, Family, Knowledge, Compliance with Hypertension Sufferers